Polymorphisms in microRNA binding sites of mucin genes as predictors of clinical outcome in colorectal cancer patients - Vymetálková, Veronika; Pardini, Barbara; Rosa, Fabio; Jiraskova, Katerina; Di Gaetano, Cornelia; Bendova, Petra; Levý, Miroslav; Veskrnova, Veronika; Buchler, Tomas; Vodickova, Ludmila; Naccarati, Alessio; Vodička, Pavel (Carcinogenesis, 2017)
Polymorphisms in microRNA (miRNA) binding sites may affect miRNA/target gene interaction, resulting in differential mRNA/protein expression and susceptibility to common diseases. Mucins have been identified as markers of adverse prognosis. We hypothesized that genetic variations in miRNA binding sites located in mucin genes may modulate signaling response and the maintenance of genomic stability ultimately affecting cancer susceptibility, efficacy of chemotherapy and survival. In this study, we analyzed the association of single nucleotide polymorphisms in predicted miRNA target sites (miRSNPs) of mucin genes with colorectal cancer (CRC) risk and clinical outcome. Thirteen miRSNPs in 9 genes were assessed in 1111 cases and 1469 controls. No strongly significant associations were observed in the case-control study. Patients carrying the CC genotype of rs886403 in MUC21 displayed a shorter survival and higher recurrence risk when compared with TT carriers [overall survival (OS): hazard ratios (HR) 1.69; 95% confidence intervals (CI) 1.13-2.46; P = 0.01 and event-free survival (EFS): HR 1.99; 95% CI 1.38-2.84; P = 0.0002, respectively]. The observed associations were more striking after stratification for tumor site (in patients with colon cancer, OS: HR 2.63; 95% CI 1.69-4.10; P < 0.0001 and EFS: HR 2.65; 95% CI 1.72-4.07; P < 0.0001). In contrast, rectal cancer cases carrying the CC genotype of rs4729655 in MUC17 displayed a longer survival (OS: HR 0.27; 95% CI 0.14-0.54; P = 0.0002) than those with the most common genotype. To our knowledge, this is the first study investigating miRSNPs potentially affecting miRNA binding to mucin genes and revealing their impact on CRC susceptibility or patient's survival.
Keywords: studie případů a kontrol; muciny; Aged; mikro RNA; staging nádorů; 3' Untranslated Regions; jednonukleotidový polymorfismus; Neoplasm Staging; genotyp; Mucins; Female; Male; Humans; lidé středního věku; prognóza; genetická predispozice k nemoci; mužské pohlaví; vazebná místa; Binding Sites; senioři; 3' nepřekládaná oblast; lidé; Prognosis; Biomarkers, Tumor; Colorectal Neoplasms; kolorektální nádory; Polymorphism, Single Nucleotide; ženské pohlaví; Genotype; Survival Rate; MicroRNAs; Middle Aged; Case-Control Studies; Follow-Up Studies; nádorové biomarkery; Genetic Predisposition to Disease; následné studie; lokální recidiva nádoru; míra přežití; Neoplasm Recurrence, Local